Evaluation Of Solar Photovoltaic Levelized Cost Of Energy For PV Grid Parity Analysis In Malaysia - Gan, Chin Kim; Lau, Cheiw Yun; Tan, Pi Hua (UM Power Energy Dedicated Advanced Centre (UMPEDAC), 2014)
The Malaysian Government, under the Renewable Energy Act 2011 and the introduction of Feed-in Tariff (FiT) scheme has identified solar Photovoltaic (PV) system as one of the promising renewable resources that could generate ‘green’ electricity for the consumers in Malaysia. This is to reduce the dependency on fossil fuels and more importantly, to tackle the climate change challenge. In this regard, achieving grid parity is the main priority for the policy makers. When the cost of PV system generation is equal to or lower than the cost of conventional fossil fuel generation; grid parity is achieved. This paper presents the detailed PV grid parity analysis for a 4kW residential grid-connected PV system based on the calculation of the Levelized Cost of Electricity (LCOE). The research is carried out based on the three key parameters that drive grid parity, namely: the PV system price, electricity tariff, and discount rate. The FiT degradation rate of solar PV system has been taken into consideration. The finding suggests that the LCOE for a 4.0 kWp system in Malaysia is RM 0.9170/kWh in 2014. This means it may take up to 16 years for Malaysia to achieve PV grid parity. In contrast, with 1% yearly degradation rate of LCOE, results suggest that Malaysia will achieve grid parity in 2029. In addition, various analyses on the sensitivity of the key drivers to grid parity in Malaysia is carried out.